O regime internacional antilavagem de capitais e a atuação do Grupo de Ação Financeira Internacional (GAFI) - Osti, Artur Barros Freitas (2024)
International society has long recognized that isolated national policies are insufficient to combat crime, given the transnational nature of certain criminal groups. It is because of the transnational nature of certain illicit acts, as well as the global concern about their practice, that Public International Law has stepped in to complement the abilities of states in dealing with criminal activity. The study's theme is the work of the Financial Action Task Force (FATF) and its research problem is the investigation into the FATF's work processes and the compliance of the domestic legal system with its Recommendations. The dissertation's general objective is to analyze the FATF's actions in anti-money laundering matters, based on emerging issues in Brazil. To carry out the qualitative research, the hypothetical-deductive method and the structuralist and historical auxiliary methods were used, with documentary and bibliographic studies. The dissertation is divided into four chapters. Initially, it presents the development of International Public Law to achieve common goals and the work of international organizations, especially the instruments used to disseminate public policies, called processes of action. The second chapter seeks to contextualize the global concern with money laundering and the internationalization of the production of criminal law within states. The third chapter deals with the evolution of the FATF, from its formation to the way it operates, with an analysis of the peculiarities of this organization in international society, especially with regard to the legal nature of its Recommendations and the forms of countermeasures applied in the event of non-compliance. The fourth and final chapter seeks to answer, within the established methodological framework, to what extent the Brazilian legal system has been adapted (harmonized) to international conventions and, above all, to the Recommendations issued by the FATF. To this end, the issue of the (im)possibility of importing the concept of “organized crime” from the Palermo Convention into Brazilian laundering law is analyzed, based on the position of the Federal Supreme Court (STF) on the matter. In order to deal with the repercussions of the FATF Recommendations in Brazil, the controversy reinstated by the STF over the sharing of Financial Intelligence Reports (FIRs) is revisited, as well as the issue of including lawyers in the list of obliged persons based on the FATF Recommendations and in the context of Brazilian legislation. The last section of this paper presents a current picture of the regulations governing fixed-odds sports betting in Brazil, in order to ascertain the anti-money laundering concerns and the influence of the FATF guidelines on this issue which, until the conclusion of this paper, has been boiling over in the news, requiring a joint national effort to understand the social, economic and cultural phenomena arising from betting. The research indicated the existence of challenges in bringing domestic legislation into line with FATF recommendations, as well as significant efforts to establish Brazil as a state committed to the international anti-money laundering regime.